2011
DOI: 10.1007/s10722-011-9729-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemotypical variation in Vanilla planifolia Jack. (Orchidaceae) from the Puebla-Veracruz Totonacapan region

Abstract: One of the threats in the diversity loss of the primary gene pool of Vanilla planifolia is the lack of information on existing level of polymorphism in cultivated germplasm, and the different expressions of this polymorphism. For this reason, it is proposed to study the chemical polymorphism of the four phytochemicals that define the vanilla aroma quality in fruits (vanillin, vanillic acid, p-hydroxybenzaldehyde, p-hydroxybenzoic acid) by HPLC analysis (High Performance Liquid Chromatography) of 25 collections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
9
0
7
Order By: Relevance
“…ex Andrews. However, the present study did not elucidate the magnitude of the interaction effect and the phytochemical characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…ex Andrews. However, the present study did not elucidate the magnitude of the interaction effect and the phytochemical characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that some AC precursors, such as lignin, FA, guaiacol, catechol, among others, are released and converted into AC such as VA, vanillic alcohol, HBA, PHB and vanillin, (Harazono et al , Ito et al ; Zamzuri et al ). Specifically, the FA has also been proposed as a precursor in the biosynthesis of vanillin and vanillin glucoside, both considered the most abundant AC in mature vanilla beans (Hernández‐Hernández ; Salazar‐Rojas et al ). Additionally, Ammar et al () demonstrated the assimilation capacity of different AC as FA by some Gram‐negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…During the process, the colour of the vanilla beans changes from green to dark brown ‘chocolate’ and there is an increase in the concentration of different aromatic compounds (AC) such as vanillin (1000–20 000 ppm), p‐hydroxybenzaldehyde (HBA) (2000 ppm), vanillic acid (VA) (4‐hydroxy‐3‐methoxy benzoic acid) (2000 ppm) and p‐hydroxybenzoic acid (200 ppm). All these compounds are responsible for the vanilla aroma (Salazar‐Rojas et al ). The process of obtaining natural vanillin is an inexpensive method compared with the biosynthetic pathway and requires physico‐chemical changes in vanilla beans and biological factors such as microbial participation (Frenkel et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Circunstancias muy similares son descritas por investigadores mexicanos relacionadas con el desconocimiento real del germoplasma de V. planifolia existente en la región de Totonacapan, Veracruz (Herrera-Cabrera et al, 2012) y otras regiones productoras de México (Castillo y Engleman, 1993). La situación es preocupante cuando muchos autores afirman que V. planifolia es originaria de México (Soto, 1999;Havkin-Frenkel y Belanger, 2007;Castro, 2008;Barrera-Rodríguez et al, 2009;Gonzalez-Arnao et al, 2009;Gigant et al, 2011;Salazar-Rojas et al, 2011;Tapia, 2011;Kelso-Bucio et al, 2012), y que a pesar de contar con gran diversidad genética para hacer fitomejoramiento, el mercado de la vainilla mexicana representa menos de un 1% de la producción mundial (Soto, 2006, Barrera-Rodríguez et al, 2009Salazar-Rojas, 2011;Herrera-Cabrera et al, 2012).…”
Section: Importancia De Vanilla Sppunclassified